Executive Option Repricing, Incentives, and Retention - Chen, Mark A. (Journal of Finance, 2004)
ABSTRACT While many firms grant executive stock options that can be repriced, other firms systematically restrict or prohibit repricing. This article investigates the determinants of firms' repricing policies and the consequences of such policies for executive turnover and retention. Firms that have better internal governance, that use more powerful stock‐based incentives, or that face less shareholder scrutiny are more likely to maintain repricing flexibility. Firms that restrict repricing are more vulnerable to voluntary executive turnover following stock price declines. When share price declines are severe, restricting firms appear to award unusually large numbers of new options.